PENERAPAN ALGORITMA BUBBLE SORT PADA SISTEM PEMINJAMAN BUKU BERBASIS WEB DI PERPUSTAKAAN SMPN 158 JAKARTA TIMUR - Rasiban,M.Kom; Muhammad Jardine Ramaddhani (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
The function of the library is a very important thing in helping students to provide the needs of textbooks and companion books in an easy and cheap way. But in reality so far there are still many obstacles related to its management, including how to control the amount of stock, calculate the number of borrowers, the number of returns and registration in lending. The condition of library management at SMP Negeri 158 Jakarta is still done manually so that it is possible for errors to occur in the circulation of borrowing and returning books because the data has not been well documented so that services are not optimal. Overcoming this, it is necessary to have a system that can facilitate the processing of data on borrowing and returning books more effectively and efficiently. Web-based library application development method PHP programming language, MySql database and Bubble Sort Algorithm.